Ternary geopolymer capable of solidifying heavy metal ions and preparation method thereof

By blending the pyrolytic residues and fly ash in the pyrolytic products of the sludge pyrolytic products with the slag and standard sand, and using alkaline active agents to form a dense network and gel, the problem that pyrolytic residues and fly ash cannot be recycled and utilized is solved, effective curing and reducing heavy metals and halogenated alkyl compounds is achieved, the risk of environmental pollution is reduced, and solid waste resource utilization is achieved.

CN119822713AActive Publication Date: 2025-04-15TIANJIN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510168241.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-15
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

Due to their special oil-containing properties, the pyrolytic residues and fly ash in the pyrolytic products of oil sludge cannot be recycled or resource-based, and they contain heavy metals and halogenated alkyl compounds, which poses a risk of environmental pollution.

Method used

By blending fly ash and pyrolyzed residue with slag and standard sand, the amount of slag and standard sand is reduced, and alkaline active agents are used to form a dense network and gel, heavy metal ions are cured and free ions and halogenated alkyl compounds are adsorbed to form a curable ternary geopolymer.

Benefits of technology

The curing rate of Pb and Mn in pyrolytic residues and fly ash is achieved by achieving a curing rate of more than 99.90% of Pb and Mn in pyrolytic residues, a reduction rate of more than 90% of Cl in fly ash, and a reduction rate of more than 80% of petroleum hydrocarbons in pyrolytic residues is achieved, which greatly reduces environmental risks and realizes the resource utilization of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822713A_ABST
    Figure CN119822713A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste recycling, in particular to a ternary geopolymer capable of solidifying heavy metal ions and a preparation method of the ternary geopolymer. The invention provides a preparation method of a ternary geopolymer capable of solidifying heavy metal ions, which comprises the following steps: mixing fly ash, pyrolysis residues, furnace slag, standard sand and an alkaline active agent to obtain a powder mixture, mixing the powder mixture with water, and solidifying to obtain the ternary geopolymer. The ternary geopolymer prepared by the invention can realize the curing efficiency of 99.90% of Pb and Mn, Cl in fly ash can be reduced by 90% or more, and petroleum hydrocarbon in pyrolysis residues can be reduced by 80% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource recovery, and in particular to a ternary geopolymer capable of solidifying heavy metal ions and a preparation method thereof. Background Art

[0002] Crude oil is the lifeblood of modern industry. In 2023, global oil production will reach 4.51 billion tons. In the process of crude oil extraction and transportation, a large amount of oil-sludge (OS) will inevitably be produced. According to statistics, 5 tons of OS will be discharged for every 1,000 tons of crude oil produced. At present, China's OS inventory has exceeded 140 million tons.

[0003] Based on its hazardous characteristics, OS has been listed as hazardous waste by many countries. Improper handling of OS will cause serious soil and groundwater pollution, and the emitted odorous gases will also enter the atmosphere, which will cause unpredictable damage to the ecological environment and human health. At present, pyrolysis can simultaneously achieve the dual goals of harmless disposal and resource utilization of OS, and has become an important disposal technology for OS. In an anaerobic or anoxic environment, OS can be degraded into high calorific value pyrolysis gas and oil at 500-800°C; at the same time, the pyrolysis residue (Pyrolysis residue, PR) is discharged from the bottom of the furnace, and the fly ash (Fly ash, FA) is collected in a bag.

[0004] The obtained PR and FA contain a small amount of total petroleum hydrocarbons (TPHs) and heavy metals (HMs). Since the oil content of PR and FA is above 0.3wt%, they cannot be directly used in agriculture. Therefore, the PR and FA produced by OS pyrolysis become unusable solid waste products. Summary of the invention

[0005] The present invention provides a ternary geopolymer capable of solidifying heavy metal ions and a preparation method thereof. The pyrolysis products of oil sludge, namely pyrolysis residue and fly ash, cannot be recycled or utilized as resources due to their special oil content. The present invention utilizes the characteristics of pyrolysis residue and fly ash containing inorganic materials such as silicon oxide, aluminum oxide, and calcium oxide, blends them with slag and standard sand, and consumes pyrolysis residue and fly ash by reducing the amount of slag and standard sand; at the same time, an available ternary geopolymer is obtained, and the solidification rate of Pb and Mn in pyrolysis residue and fly ash is above 99.90%, the reduction rate of Cl in fly ash is above 90%, and the reduction rate of petroleum hydrocarbons in pyrolysis residue is above 80%; the environmental risks of pyrolysis residue and fly ash are greatly reduced, and solid waste resource utilization is realized.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a preparation method of a ternary geopolymer capable of solidifying heavy metal ions, comprising: mixing fly ash, pyrolysis residue, slag, standard sand and an alkaline active agent to obtain a powder mixture, and mixing the powder mixture with water and solidifying the mixture to obtain a ternary geopolymer; the fly ash and the pyrolysis residue are both pyrolysis products of oily sludge, and the oil content in the pyrolysis residue is 2-3wt%;

[0008] The fly ash comprises, by weight, 48 to 50 parts of CaO, 1 to 2 parts of SiO2, 0.5 to 1 parts of Al2O3, 1 to 1.5 parts of Fe2O3, 1 to 1.5 parts of MgO, 6 to 7 parts of Na2O, 10 to 11 parts of K2O, 8 to 9 parts of SO3, 0.5 to 1 part of BaO, 0.1 to 0.2 parts of PbO, 2 to 3 parts of halogenated alkane compounds, 11 to 12 parts of free chlorine, and 4 to 5 parts of free fluorine;

[0009] The components of the pyrolysis residue are: by weight, including 12 to 13 parts of CaO, 25 to 28 parts of SiO2, 7 to 9 parts of Al2O3, 6 to 7 parts of Fe2O3, 2 to 3 parts of MgO, 1 to 2 parts of Na2O, 1 to 1.5 parts of K2O, 14 to 15 parts of SO3, 14 to 15 parts of BaO, 0.2 to 0.3 parts of TiO2, 0.01 to 0.05 parts of PbO, 0.1 to 0.2 parts of MnO, 9 to 10 parts of halogenated alkane compounds, and 0.2 to 0.4 parts of free chlorine;

[0010] The components of the slag are: by weight, including 30 to 35 parts of CaO, 28 to 33 parts of SiO2, 16 to 18 parts of Al2O3, 0.2 to 0.4 parts of Fe2O3, 10 to 11 parts of MgO, 0.5 to 0.7 parts of Na2O, 0.3 to 0.4 parts of K2O, 2 to 3 parts of SO3, 0.8 to 0.9 parts of TiO2, 0.2 to 0.3 parts of MnO, 2 to 3 parts of halogenated alkane compounds, and 0.05 to 0.07 parts of free chlorine.

[0011] Fly ash has a smaller particle size and its composition is similar to that of slag, so it can be used to replace slag; while the pyrolysis residue has a larger particle size and can replace standard sand used as aggregate. In addition, fly ash and pyrolysis residue have a multi-level pore structure, which is convenient for adsorbing and locking free ions. Among them, the pyrolysis residue and fly ash used in the present invention are pyrolysis products of oil sludge, so the pyrolysis residue contains a small amount of oil. The organic matter in the oil may change the distribution of water in the hydration process by absorbing water, thereby resulting in weak local hydration reaction and insufficient strength in some areas. In addition, the saturated light hydrocarbons in the oil are easy to volatilize during the hydration stage to form holes and microcracks, which greatly reduce the strength of the material.

[0012] Furthermore, considering that, under normal circumstances, the overall strength of geopolymers will drop significantly after the introduction of solid wastes such as fly ash; therefore, small-particle fly ash is added to replace part of the slag, and large-particle pyrolysis residue is used to replace part of the standard sand, to construct a richer particle grading and slow down the drastic strength drop after the addition of fly ash and pyrolysis residue.

[0013] Solid waste composed of fly ash and pyrolysis residue, together with slag and standard sand, can be used as a ternary Si-Al-Ca precursor. When an alkaline activator is added, the Si-Al-Ca precursor further forms a dense network and gel. During the alkali activation process, heavy metals Pb and Mn in fly ash and pyrolysis residue are solidified in the gel grid structure, free chlorine and free fluorine are adsorbed in the porous structure of fly ash and pyrolysis residue and on the surface of inorganic particles in the gel grid, and halogenated alkyl compounds can be adsorbed in the three-dimensional network structure and fixed in the ternary geopolymer in the form of physical adsorption or chemically bonded with the active component aluminosilicate to be fixed in the ternary geopolymer; thus, while obtaining the ternary geopolymer, the heavy metal leaching problem, chlorine leaching, and halogenated alkyl compound pollution problem can be solved, achieving safe protection of the environment.

[0014] Preferably, the mass ratio of the fly ash to the slag is 1:2 to 1:9, the mass ratio of the pyrolysis residue to the standard sand is 1:2 to 1:9, and the mass ratio of the slag to the standard sand is 1:3.

[0015] Further preferably, the mass ratio of the fly ash to the slag is 1:3 to 1:5, the mass ratio of the pyrolysis residue to the standard sand is 1:3 to 1:5, and the mass ratio of the slag to the standard sand is 1:3.

[0016] Further preferably, the mass ratio of the fly ash to the slag is 1:3.5-1:4.6, the mass ratio of the pyrolysis residue to the standard sand is 1:3.5-1:4.6, and the mass ratio of the slag to the standard sand is 1:3.

[0017] Further preferably, the mass ratio of the fly ash to the slag is 1:4, the mass ratio of the pyrolysis residue to the standard sand is 1:4, and the mass ratio of the slag to the standard sand is 1:3.

[0018] Further preferably, the mass ratio of the fly ash to the slag is 1:4 to 1:9, the mass ratio of the pyrolysis residue to the standard sand is 1:4 to 1:9, and the mass ratio of the slag to the standard sand is 1:3.

[0019] Further preferably, the mass ratio of the fly ash to the slag is 1:9, the mass ratio of the pyrolysis residue to the standard sand is 1:9, and the mass ratio of the slag to the standard sand is 1:3.

[0020] Preferably, the amount of the alkaline activator is 28 to 32 parts by weight based on the sum of the weight of the fly ash and the slag.

[0021] Further preferably, the amount of the alkaline activator used is 30 parts by weight based on the sum of the weight of the fly ash and the slag.

[0022] Preferably, the alkaline active agent is sodium hydroxide and sodium silicate.

[0023] Preferably, the mass ratio of the powder mixture to the water is (5-8):1.

[0024] Preferably, the particle size of the fly ash is 5 to 10 μm, the particle size of the pyrolysis residue is 30 to 50 μm, the particle size of the slag is 5 to 10 μm, and the particle size of the standard sand is 0.08 to 2 mm.

[0025] Particles of different sizes can fill different voids and help form a more compact microstructure; the gradient particle size design also helps improve the fluidity and construction performance of the ternary geopolymer. Micron-sized particles of fly ash, slag and pyrolysis residue can provide better mechanical properties on a macro scale and help form a continuous three-dimensional network structure. Millimeter-sized particles of standard sand are mainly used as aggregates to increase the stability of the material, prevent shrinkage cracking, and improve compressive strength.

[0026] Preferably, the curing conditions are: curing at 20-25° C. for 1-2 days; then curing at 20-25° C. and 55-65% humidity for 7-28 days.

[0027] The present invention also provides a ternary geopolymer capable of curing heavy metal ions obtained by the above preparation method, wherein the curing rates of Pb and Mn are both above 99.90%, the reduction rate of Cl in fly ash is above 90%, and the reduction rate of petroleum hydrocarbons in pyrolysis residue is above 80%.

[0028] Preferably, after 30 days of freeze-thaw cycles or 30 days of acid rain erosion, the compressive strength of the ternary geopolymer capable of curing heavy metal ions is more than 95% of the compressive strength of the ternary geopolymer capable of curing heavy metal ions after curing for 28 days.

[0029] Therefore, the present invention has the following beneficial effects:

[0030] (1) The present invention uses fly ash to replace part of the slag and pyrolysis residue to replace part of the standard sand, thereby solving the solid waste pollution problem of fly ash and pyrolysis residue and obtaining a ternary geopolymer material that meets the application standards.

[0031] (2) The present invention ensures the strength of the ternary geopolymer by compounding the ratio of fly ash to slag, the ratio of pyrolysis residue to standard sand, and the gradient particle size of fly ash, pyrolysis residue, slag, and standard sand, and the obtained ternary geopolymer can still maintain a high compressive strength under extreme environments such as extreme cold and acid rain.

[0032] (3) The ternary geopolymer preparation method provided by the present invention can achieve a solidification efficiency of 99.90% for Pb and Mn in pyrolysis residue and fly ash, and achieve a reduction of more than 90% in Cl in fly ash, and a reduction of more than 80% in petroleum hydrocarbons in pyrolysis residue. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 PSD and SEM images of fly ash, pyrolysis residue and slag, where a~c are the PSD images of fly ash, pyrolysis residue and slag, and d~f are the SEM images of fly ash, pyrolysis residue and slag;

[0034] Figure 2 XRD patterns of fly ash, pyrolysis residue and slag;

[0035] Figure 3 is the curing ability diagram of the ternary geopolymer, where a is the curing ability of Pb, b is the curing ability of Mn, c is the curing ability of chloride ions, and d is the curing ability of TPHs;

[0036] Figure 4 is the strength of the ternary geopolymer, where a is the compressive strength at 7d and 28d, and b is the compressive strength ratio of 7d / 28d;

[0037] Figure 5 is the mass loss result of freeze-thaw cycle and acid rain corrosion, where a is the mass loss of ternary geopolymer under 30 freeze-thaw cycles, c is the loss rate of ternary geopolymer under 30 freeze-thaw cycles, b is the mass loss of ternary geopolymer under 30 days of acid rain corrosion, and d is the loss rate of ternary geopolymer under 30 days of acid rain corrosion;

[0038] Figure 6 The results of the environmental risk assessment of geopolymers after the 30-day durability test, where a is the Pb leaching concentration, b is the Mn leaching concentration, c is the Cl content, and d is the TPHs content;

[0039] Figure 7 is the compressive strength result of ternary geopolymer, where a is the compressive strength of ternary geopolymer after 30-day durability test, and b is the ratio of the compressive strength of ternary geopolymer after 30-day durability test to that of 28-day-old;

[0040] Figure 8 The actual picture of the F00P00 sample fragments, where a is 28 days of curing, b is 30 days of freeze-thaw cycle, and c is 30 days of acid rain corrosion;

[0041] Fig. 9 Comparative analysis of the hydration characteristics of F00P00 under different conditions, where a is the XRD diffraction pattern, b is the FTIR spectrum, c is the TG curve, d is the DTG curve, e1 is the SEM image after freeze-thaw cycles, and e2 is the SEM image after acid rain corrosion. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0043] [Example]

[0044] The slag in this part was purchased from Longze Water Purification Materials Co., Ltd. in Gongyi City, Henan Province, with a particle size of 5 to 10 μm; the standard sand was purchased from Xiamen AIS Standard Sand Co., Ltd., which is the statutory reference material equivalent to the international standard ISO679 for testing cement strength, with a particle size of 0.08 to 2 mm; sodium hydroxide (NaOH), with a purity of 95%, was purchased from Myrrel; sodium silicate (Na2O·2SiO2), with a purity of 98%, was purchased from Myrrel.

[0045] In this section, fly ash and pyrolysis residue are products obtained by pyrolysis of oily sludge. The specific components of fly ash, pyrolysis residue and slag are shown in Tables 1 and 2, and the specific composition of oily sludge is shown in Tables 3 and 4:

[0046] Table 1 Chemical composition Table 1

[0047]

[0048] Table 2 Chemical composition Table 2

[0049]

[0050] Table 3 Element composition of oily sludge (wt.%)

[0051]

[0052] Table 4 Industrial analysis of oily sludge (wt.%)

[0053]

[0054] Example 1

[0055] According to the proportions in Table 5, fly ash, pyrolysis residue, slag, standard sand and alkaline active agent were weighed and stirred for 120 seconds, and water was added and mixed for 120 seconds to obtain a uniform mortar. The mortar was poured into a mold, cured at room temperature for 1 day, and then demolded, and then cured in a constant temperature and humidity environment (20°C, 60%) for 7 days or 28 days. Among them, the alkaline active agent with a modulus of 1.5 was obtained by mixing sodium hydroxide and sodium silicate.

[0056] Except for the specific formula referring to Table 5, the preparation methods of the other embodiments and comparative examples are exactly the same as those in Example 1.

[0057] Table 5 Proportions of ternary geopolymers

[0058]

[0059]

[0060]

Performance test

[0061] 1. Performance evaluation of fly ash and pyrolysis residue

[0062] Toxicity evaluation and heavy metal leaching experiments were conducted on fly ash and pyrolysis residue, and the results are shown in Tables 6 and 7.

[0063] Table 6 Toxicity evaluation of fly ash and pyrolysis residue

[0064]

[0065] Table 7 Heavy metal leaching results of fly ash and pyrolysis residue (mg / L)

[0066]

[0067] The heavy metal leaching results of fly ash and pyrolysis residue obtained in Table 7 are compared with the standards proposed by the U.S. Environmental Protection Agency, the "Hazardous Waste Identification Standard-Leaching Toxicity Identification" stipulated in GB5085.3-2007, the "Urban Domestic Waste Landfill Pollution Control Standard" stipulated in GB16889-2008, and the "Hazardous Waste Landfill Pollution Control Standard" stipulated in GB18598-2019. The heavy metal leaching amounts all meet the emission standards. Among them, the leaching amounts of Pb in fly ash and Mn in pyrolysis residue are large, which may cause environmental safety problems in production and application.

[0068] 2. Morphology evaluation of fly ash, pyrolysis residue and slag

[0069] PSD test was carried out on fly ash, pyrolysis residue and slag, and the results were as follows: Figure 1 a~ Figure 1c. It can be seen from the observation that the fly ash and the pyrolysis residue have a multi-level pore structure, the average particle size of the fly ash is 6.2μm, and the average particle size of the slag is 6.3μm. From the analysis of particle size and composition, the fly ash can be used as a replacement material for slag; while the particle size of the pyrolysis residue is larger, with an average particle size of 37.9μm.

[0070] SEM tests were performed on fly ash, pyrolysis residue and slag, and the results are as follows: Figure 1 d~ Figure 1 It can be seen from the observation that fly ash, pyrolysis residue and slag appear as irregular particles of different sizes, and their particle size range is consistent with the results of PSD.

[0071] XRD tests were performed on fly ash, pyrolysis residue and slag, and the results are as follows: Figure 2 As shown in the figure, it can be observed that the peaks corresponding to the important components in Table 1 and Table 2 can all be detected by XRD.

[0072] 3. Performance evaluation of ternary geopolymer

[0073] ① Solidification ability of heavy metals / Cl / TPHs

[0074] The curing ability of the ternary geopolymers or geopolymers prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was tested for Pb, Mn, chloride ions and TPHs, respectively. The results are as follows: Figure 3 shown.

[0075] observe Figure 3 a and Figure 3 b It can be seen that: from the observation of the three groups of data of F10P00, F20P00 and F30P00, it can be seen that as the amount of fly ash added increases, its inherent Pb content is high, so the Pb curing ability of the corresponding ternary geopolymer decreases, while the Mn curing ability of the corresponding ternary geopolymer increases. The ternary geopolymers or geopolymers prepared in Examples 1 to 3 and Comparative Examples 1 to 7 have Pb and Mn curing abilities of more than 98%, and the ternary geopolymers prepared in Examples 1 to 3 have Pb and Mn curing abilities of more than 99.90%.

[0076] In addition, the ternary geopolymers obtained in Examples 1 to 3 also have a good chloride ion curing efficiency, which can reach more than 87%; the curing efficiency for TPHs is more than 63%, which can fix most of the petroleum hydrocarbons and solve the problem that the oil in fly ash and pyrolysis residues hinders their resource utilization.

[0077] ② Strength

[0078] The compressive strength test of the ternary geopolymers or geopolymers prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was performed, and the results are as follows: Figure 4 shown.

[0079] observe Figure 4 It can be seen from a that with the addition of fly ash and pyrolysis residue, the compressive strength of the ternary geopolymer decreased significantly. Figure 4 b It can be seen that the compressive strength of the geopolymers in the three formulas of F10P00, F20P00 and F20P60 after curing for 7 days is higher than the compressive strength after curing for 28 days. The strength ratios of F10P00 and F20P00 are slightly higher than 100%, and the strength ratio of F20P60 reaches 105%.

[0080] ③Durability

[0081] The ternary geopolymers or geopolymers obtained in Examples 1 to 3 and Comparative Example 1 were subjected to a 30-day freeze-thaw cycle test and a 30-day acid rain corrosion test. The test method is as follows, and the results are recorded in Figures 5 to 9 shown.

[0082] Test method: Immerse the geopolymer sample in 20±2℃ distilled water for 48 hours to saturate the internal water. Then wipe the sample dry and let it stand for 30 minutes. Freeze-thaw cycle experiment: Freeze the geopolymer in a -20±2℃ environment for 12 hours, then immerse the sample in 20±2℃ water for 12 hours, where the water level is 20mm higher than the top of the test block. After 6, 12, 18, 24 and 30 freeze-thaw cycles, test the performance of the sample. Acid rain corrosion experiment: The main components of acid rain are sulfuric acid and nitric acid. my country is a sulfuric acid acid rain country because SO4 2- The contribution to acid rain acidity is much higher than that of NO3 - . It is reported that acid rain with a pH value between 3.0 and 5.0 will seriously affect the mechanical properties and durability of concrete. In this study, sulfuric acid and nitric acid were used to simulate acid rain with a pH value of 3.0, and the molar ratio of sulfuric acid to nitric acid was set to 9:1. The weighed samples were immersed in the simulated acid rain solution, in which the solution level was 20 mm above the top of the test block. The performance of the samples was tested after 6d, 12d, 18d, 24d and 30d.

[0083] 1) Quality loss results

[0084] After 30 freeze-thaw cycles and 30 days of acid rain corrosion, the mass loss and loss rate of the samples are as follows: Figure 5 As shown. Overall, the samples have good stability. Under the continuous action of freeze-thaw cycles, the structure of the samples was destroyed and the mass loss continued to increase. However, even after 30 tests, the mass loss was still maintained within 1% ( Figure 5 c). The possible reason is that during the freeze-thaw cycle, water may further participate in the reaction and constitute the bound water part of the hydration product, while part of the water is absorbed and stored in the pores, both of which delay the mass loss of the sample.

[0085] The mass change caused by 30-day acid rain corrosion can be roughly divided into three stages. After 6 days of acid rain corrosion, the mass loss of the sample continued to increase and reached the highest value (about 1-2%). In this process, particles were observed to fall off the surface of the specimen. + and SO4 2- Under the joint corrosion of CaO and Al2O3, CaO and Al2O3 were corroded and dissolved, resulting in mass loss. During the 6-24d corrosion process, the mass loss of the sample showed a continuous decrease. This interesting phenomenon may come from two aspects. One is that during the immersion process, water continuously penetrated into the geopolymer matrix through the pores on the surface of the block and participated in the hydration reaction. The other is that SO4 2- With some cations (such as Mg 2+ , Fe 2+ and Zn 2+ ) combine to form crystals, which fill the pores and increase the density of the matrix. In the stage of 24 to 30 days, the mass loss of all samples began to increase. This means that the corrosion of acid rain has once again taken the dominant position, and the new hydration products can no longer make up for the particle shedding caused by the destruction of the sample structure. The hydrated silicate on the surface of the corroded specimen is transformed into CaSO4, and the viscosity of the aggregate and gel is reduced, which directly leads to the shedding of fine sand. From a longer-term perspective, after the sample has undergone freeze-thaw cycles and acid rain corrosion, the continuous loss of mass is an inevitable trend, which will eventually lead to the collapse of the sample structure.

[0086] 2) Environmental risk assessment

[0087] In actual application, solid waste-based building materials often expose greater environmental risks after long-term environmental degradation, so it is necessary to conduct environmental risk assessment on the samples after durability testing. It is not difficult to find that freeze-thaw cycles and acid rain corrosion have no significant impact on the solidification ability of harmful substances in ternary geopolymers. Figure 6 a and Figure 6 b shows the leaching and stabilization efficiency of typical heavy metals in the ternary geopolymers F10P30, F20P60 and F30P90. The leaching concentrations of Pb and Mn in the samples were both lower than 0.01 mg / L, and the corresponding heavy metal stabilization efficiency was still able to remain above 99%. Figure 6 c and Figure 6 It can be seen that the ternary geopolymer has reduced the chloride ion and TPHs content in solid waste by more than 90% and 60% respectively, and the encapsulation effect of the geopolymer matrix on inorganic ions and organic matter has not been weakened. In short, after the durability test, the ternary geopolymer still shows the characteristics of low environmental risk.

[0088] 3) Compressive strength

[0089] Figure 7 The compressive strength results of the samples after 30 days of freeze-thaw cycles and acid rain corrosion are shown. Surprisingly, compared with the samples with conventional curing for 28 days, all durability test samples showed a strength retention rate of more than 95%. What is more noteworthy is that the strength of most samples is even higher than that of conventionally cured samples. After 30 days of acid rain corrosion, the compressive strength of sample F00P00 reached nearly 90MPa, which is 1.15 times that under conventional curing conditions. It can be seen that whether it is a freeze-thaw cycle or an acid rain corrosion process, after a long period of immersion, water participates in the hydration reaction of the sample, and the hydration products increase to form a more compact matrix. The compressive strength of the sample after freeze-thaw cycles is slightly lower than that of the acid rain corrosion sample, which is likely related to the experimental process, that is, the freeze-thaw process of the sample is an intermittent immersion process, and the degree of development of the hydrated gel is generally lower than that of the sample after continuous acid rain immersion.

[0090] 4) Hydration characteristics

[0091] Sample F00P00 was selected as a reference to further compare and analyze the hydration characteristics of geopolymer samples under deteriorated conditions. Figure 8 It can be clearly observed that the interior of the 28d curing sample is grayish white, and the whole is dry and brittle. The interior of the samples after the 30d durability test is dark gray, and the matrix is ​​tightly connected to the sand and gravel. This corresponds to the results of the compressive strength. Obviously, Figure 8 b and Figure 8 The sample in c absorbed more water, and the development of hydration products was more complete.

[0092] In order to gain a deeper understanding of the differences in the hydration characteristics of the samples under different environments, a series of characterizations were performed. Fig. 9 a shows the XRD diffraction pattern of F00P00. There are obvious differences in the peak intensities representing quartz and calcite (or C-(A)-SH gel), mainly manifested in that the diffraction peak of the acid rain corrosion sample is the strongest, followed by the freeze-thaw cycle sample, and the conventional curing sample is the lowest. This is again consistent with the compressive strength of the sample ( Figure 7 ) corresponds to. In addition, the FTIR spectrum shows that ( Fig. 9 b), the bands representing (C,N)-ASH, Si-OT and Si-O are significantly different. The peak area of ​​the sample after durability test is larger, which indicates that the chemical environment of Si has changed and a gel with a higher degree of polymerization has been generated in the system. The TG curve shows that the stability of the acid rain corrosion sample is slightly higher than that of the freeze-thaw cycle sample, and both are significantly higher than the 28d sample ( Fig. 9c). The mass loss of F00P00 can be roughly divided into two stages. The first stage is mainly the dehydration process of hydration products between 30 and 200 °C, while the second stage mainly represents the dehydration and decarbonization behavior of a small number of other products and calcite at 200 to 750 °C. Corresponding to the DTG curve, it can be found that the peak area of ​​the 28d sample at 30 to 200 °C is significantly higher than the other two. However, this does not mean a decrease in the content of hydration products. After the sample has undergone a more sufficient hydration reaction, the degree of polymerization of the C-(A)-SH gel is improved and the amount of bound water is reduced, which will ultimately promote the strength development of the sample. At the same time, there are obvious differences in the SEM microscopic images of the samples under different environments. The gel of the sample that has undergone freeze-thaw cycles is smoother and denser, and a small amount of scattered gel particles are distributed on the matrix ( Fig. 9 e1). Fig. 9 e2 observed that the gel clumps and layered gels of the acid rain corrosion samples were glued together and tightly attached to the fine sand particles. Overall, after the 30-day durability test, the simulated harsh environment did not cause obvious damage to the samples. Instead, the hydration reaction was promoted and the gel developed better, which also confirmed the high stability and strong anti-deterioration ability of geopolymers.

Claims

1. A method for preparing a ternary geopolymer capable of curing heavy metal ions, characterized in that: include: Fly ash, pyrolysis residue, slag, standard sand and alkaline active agent are mixed to obtain a powder mixture, and the powder mixture is mixed with water and solidified to obtain a ternary geopolymer; the fly ash and the pyrolysis residue are both pyrolysis products of oily sludge, and the oil content in the pyrolysis residue is 2-3wt%; The fly ash comprises, by weight, 48 to 50 parts of CaO, 1 to 2 parts of SiO2, 0.5 to 1 parts of Al2O3, 1 to 1.5 parts of Fe2O3, 1 to 1.5 parts of MgO, 6 to 7 parts of Na2O, 10 to 11 parts of K2O, 8 to 9 parts of SO3, 0.5 to 1 part of BaO, 0.1 to 0.2 parts of PbO, 2 to 3 parts of halogenated alkane compounds, 11 to 12 parts of free chlorine, and 4 to 5 parts of free fluorine; The components of the pyrolysis residue are: by weight, including 12 to 13 parts of CaO, 25 to 28 parts of SiO2, 7 to 9 parts of Al2O3, 6 to 7 parts of Fe2O3, 2 to 3 parts of MgO, 1 to 2 parts of Na2O, 1 to 1.5 parts of K2O, 14 to 15 parts of SO3, 14 to 15 parts of BaO, 0.2 to 0.3 parts of TiO2, 0.01 to 0.05 parts of PbO, 0.1 to 0.2 parts of MnO, 9 to 10 parts of halogenated alkane compounds, and 0.2 to 0.4 parts of free chlorine; The components of the slag are: by weight, including 30 to 35 parts of CaO, 28 to 33 parts of SiO2, 16 to 18 parts of Al2O3, 0.2 to 0.4 parts of Fe2O3, 10 to 11 parts of MgO, 0.5 to 0.7 parts of Na2O, 0.3 to 0.4 parts of K2O, 2 to 3 parts of SO3, 0.8 to 0.9 parts of TiO2, 0.2 to 0.3 parts of MnO, 2 to 3 parts of halogenated alkane compounds, and 0.05 to 0.07 parts of free chlorine.

2. The preparation method according to claim 1, characterized in that The mass ratio of the fly ash to the slag is 1:2 to 1:9, the mass ratio of the pyrolysis residue to the standard sand is 1:2 to 1:9, and the mass ratio of the slag to the standard sand is 1:

3.

3. The preparation method according to claim 1, characterized in that: The amount of the alkaline activator used is 28 to 32 parts by weight based on the total weight of the fly ash and the slag.

4. The preparation method according to claim 1 or 3, characterized in that: The alkaline active agent is sodium hydroxide and sodium silicate.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the powder mixture to the water is (5-8):

1.

6. The preparation method according to claim 1 or 2, characterized in that: The particle size of the fly ash is 5 to 10 μm, the particle size of the pyrolysis residue is 30 to 50 μm, the particle size of the slag is 5 to 10 μm, and the particle size of the standard sand is 0.08 to 2 mm.

7. The preparation method according to claim 1, characterized in that: The curing conditions are: curing at 20-25° C. for 1-2 days; then curing at 20-25° C. and 55-65% humidity for 7-28 days.

8. The ternary geopolymer capable of curing heavy metal ions obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The solidification rates of Pb and Mn are both above 99.90%, the reduction rate of Cl in fly ash is above 90%, and the reduction rate of petroleum hydrocarbons in pyrolysis residue is above 80%.

9. The ternary geopolymer capable of curing heavy metal ions according to claim 8, characterized in that: After 30 days of freeze-thaw cycles or 30 days of acid rain erosion, the compressive strength of the ternary geopolymer capable of curing heavy metal ions is more than 95% of the compressive strength of the ternary geopolymer capable of curing heavy metal ions after curing for 28 days.

Citation Information

Patent Citations

  • Modified cement stabilized macadam based on oily sludge pyrolysis residues and preparation method thereof

    CN116354649A

  • Preparation method of pavement base concrete based on oily sludge structure

    CN118388179A

  • Oily sludge-based foam light soil and preparation method thereof

    CN119330671A

  • Ultra-high strength hot-pressed geopolymeric composition and production method thereof

    US20180244572A1